PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI UPAYA PEMASARAN POTENSI AGROWISATA DI DESA CATUR KECAMATAN KINTAMANI BANGLI - Sagita, P. A. W.; Sudiarta, I. N.; Negara, I. M. K.; Karini, N. M. O. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
CaturVillage which located in Kintamani District Bangli Regency known as producer of agricultural products with quite good quality. One of the favored is arabica coffee better known by the brand “Kintamani Bali Coffee”. Beautiful natural scenery and cultural uniqueness, which also there in Catur Village have chance to attract tourists to visit. The purpose of this community service is to respond the Catur Village people's expectations who intend to raise the agro- tourism potential up to increase revenue. In the early stages, thing to do is to identify the existing tourism potential. Information technology application then considered essential to achieve the potential demand with limited resources. In this service, a website has been built with domain name www.caturvillage.com integrated with some social media such as Facebook, Twitter, and Google+. Information of Catur Village tourism potential put in article posted on those various electronic media. Catur Village people especially the young generation were given the website and social media understanding as well as the operating procedure. It is expected to help the villagers to market the existing agro-tourism potential.